2014
DOI: 10.1021/am5001135
|View full text |Cite
|
Sign up to set email alerts
|

A Cu2+ ion–F Center Complex View on the Photoluminescence Quenching and Correlating Ferrimagnetism in (Cu2+/Cu12+)0.044Zn0.956O Electrospun Nanobelts

Abstract: Unlike to the most previous reports, mixed-cation Cu(+)/Cu(2+) doping-induced novel nanoscale phenomena, including photoluminescence quenching and a correlating ferrimagnetism with Néel temperature ≈ 14 K, were found in the as-calcined (Cu2(+)/Cu1(2+))0.044Zn0.956O electrospun nanobelts (NBs). There is also high strain (up to 1.98%) and shrunk lattice distortion (ΔV/V0 ∼ 0.127%) in the (Cu2(+)/Cu1(2+))0.044Zn0.956O NBs, leading to broken lattice symmetry in conjunction with nonstoichiometry (i.e., oxygen vacan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…14,15 Therefore, studies to determine the mechanism for the interactions of localized spins associated with native point defects have been carried out. 16 Numerous theoretical [17][18][19] and experimental 13,[20][21][22][23][24] studies related to DMS demonstrated that it is possible to achieve ferromagnetism above room temperature via the substitution of cations with transition metal (TM) ions. However, the occurrence of undesirable phase separation may cause problems with TM-doped DMS, which may deter their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Therefore, studies to determine the mechanism for the interactions of localized spins associated with native point defects have been carried out. 16 Numerous theoretical [17][18][19] and experimental 13,[20][21][22][23][24] studies related to DMS demonstrated that it is possible to achieve ferromagnetism above room temperature via the substitution of cations with transition metal (TM) ions. However, the occurrence of undesirable phase separation may cause problems with TM-doped DMS, which may deter their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the ultra-low-field (i.e., giant Landé factor g ∼ 20.6839), weak, and broad EPR line character of the air-calcined and N 2 -annealed 2D h-BN nanoplates, remarkably, there is only one strong symmetric EPR peak signal in NH 3 -annealed 2D h-BN nanoplates at g ∼ 2.1267 at room temperature (295 K), and g ∼ 2.5892 at 95 K, respectively. It provides clear EPR evidence for an unpaired electron trapped in the ammoniated 2D h-BN as a paramagnetic center , where bound magnetic polarons in DMSs could be activated. , The deviation of the g -factor from that of the free electron g -value ( g e ∼ 2.0023) is susceptible to the spin–orbit coupling parameter, suggesting that the electron does not freely exist (the dotted line and arrow are drawn to guide the eye); that is, there is some sort of correlation between electron and B atom site (i.e., localized charge states) in the ammoniated 2D h-BN nanoplates (see the following discussion).…”
Section: Resultsmentioning
confidence: 99%
“…The EPR spectrum showed similar ngerprints in the main region of the EPR spectra at g z 2. 28,29 The broad resonance signal at g ¼ 2.094 is a characteristic of Cu 2+ ion. The EPR results are in good agreement with the XRD and XPS analyses.…”
Section: Results and Conclusionmentioning
confidence: 99%